O futebol no interior de Minas Gerais: os significados do torcer pelo Esporte Clube Democrata - Tiago Felipe da Silva (2011)
This study sought to investigate the foundations of the social relations and meanings of cheering for the Esporte Clube Democrata, a soccer team from Governador Valadares city, in the state of Minas Gerais, Brazil. The goals that led this study were: (1) to analyze why people have become fans of that team, (2) to examine how fans prosecute the cheering, and (3) to understand the meanings that fans assign to being a fan of Democrata team. The investigative research was guided by a qualitative approach, which sought a dialogue between the emerging data in the study and the authors that discuss especially soccer, leisure and cheering. To achieve the pursued objectives, I made use of field notes, observations and interviews. 14 fans were selected for the interviews, taking into account the variation of sex, age and "group" (organized fans, symbol fans and common fans). Data collection was performed in 2010 at two different times: first, during the participation of the Esporte Clube Democrata team in the State Championship in 2010, when I accompanied the team and selected the informants for research; later I performed the interviews with the fans. The results of this work have allowed to realize three basic meanings assigned to cheering for Esporte Clube Democrata team: (1) the relationship with the city, motivation that drives fans to associate cheering for the team to cheering for the city and to the feeling of belonging to the city; under this aspect, being a Democrata fan means being a Governador Valadares citizen; (2) the membership to the fan club, expressed by the cheering for the team and by the feeling of belonging to it, in a relationship of giving, generosity and passion for the team; and (3) the relationship with the leisure, at which point the fan falls within the "city cheering party", a meaning also related to sociability and fun made possible by the soccer matches held in the city.